2016
DOI: 10.1177/0266666916675016
|View full text |Cite
|
Sign up to set email alerts
|

Sources of agricultural information for women farmers in Tanzania

Abstract: Women farmers constitute the vast majority of agricultural producers in Tanzania; however, it is not clear where they obtain information on modern farming innovations. Knowing these sources will enable the government and international aid organizations to more effectively channel information for increased productivity, leading to national food security, increased incomes for farm families and promoting gender parity in Tanzania. This study, which was carried out among 300 women farmers in Hai and Kilosa distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…The observation that mass media-based sources were not preferred does not agree with the previous findings by Motiang and Webb (2015) and Mtega et al (2016) who found that radio and television were significant sources of information for the smallholder farmers. Also, a study by Isaya (2016) showed that over 50% of the women farmers used radio as a primary source of information. Failure by farmers to use mass media sources in the current study could be attributed to factors such as non-availability of support infrastructure, high costs of electronic gadgets and servicing fees (Brhane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that mass media-based sources were not preferred does not agree with the previous findings by Motiang and Webb (2015) and Mtega et al (2016) who found that radio and television were significant sources of information for the smallholder farmers. Also, a study by Isaya (2016) showed that over 50% of the women farmers used radio as a primary source of information. Failure by farmers to use mass media sources in the current study could be attributed to factors such as non-availability of support infrastructure, high costs of electronic gadgets and servicing fees (Brhane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of such preferences for female extension officers, the number of female extension officers is still small in Tanzania (Due et al, 1997;Isaya, 2016). However, unlike the Ethiopian farmers, the Tanzanian female farmers acknowledge that they receive adequate support by extension officers and that they are not considered less of a farmer in comparison to their husbands.…”
Section: Assessment Of Extension Deliverymentioning
confidence: 99%
“…The importance of delineating information sources is highlighted by Adegbola and Gardebroek (2007), who found group differences in adoption behaviour between farmers informed by extension agents and those informed by fellow farmers. Isaya, Agunga and Sanga (2016) also emphasised the importance of understanding how rural farmers source their information; this, in their view, enables the dissemination of effective communication using accessible channels to the targeted audience.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…These messages are communicated using available channels (C), which may include ICT-enhanced tools, often used interchangeably when referring to information sources in the literature (Msoffe and Ngulube, 2017;Osei et al, 2016). These channels (sources) are considered worthy of researching to provide insight on how farmers receive (R) information (Isaya et al, 2016), and in this instance, the effect (E) is considered as their action or feedback to the market actors.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%